PENGEMBANGANLKPD MENULIS TEKS CERPEN BERBASIS INKUIRI UNTUK SISWA SMP KELAS IX - Fahreza Chandra W; Muhammad Fuad; Edi Suyanto (Universitas Lampung, 2020)
The purpose of this study was to produce an Inquiry-based Student Activity Sheet (LKPD) on the subject matter of writing short text and testing its feasibility in learning to write short text on junior high school students. The research method used in this research is research and development (Research and Development). Data collection techniques through interviews and questionnaires in three schools, namely SMPN 1 Bengkunat, SMPN 2 Bengkunat, and SMPN 3 Bengkunat. The results showed that 1) successfully developed teaching materials in the form of LKPD based on inquiry in writing short text, 2) the overall feasibility of LKPD was declared